An inexpensive antigen for serodiagnosis of Chagas”™ disease. - Luis Briceño, Luis Briceño; Rodríguez, Eva Mary; Medina, Mehudy; Campos, Yelitza; Mosca, Walter; Briceño, Amanda; León, Graciela (Investigación Clínica, 2013)
Â  In this prospective study we evaluated the performance characteristics of a specific and sensitive antigen preparation (AgA) used in an enzyme-inked immunosorbent assay (ELISA) for the detection of anti Trypanosoma cruzi antibodies in serum samples, for Chagas”™ disease diagnosis. The antigen production was achieved by combination of nutritional stress and autoclaving the parasites. Specificity and sensitivity were evaluated in two separate tests, using 152 sera from healthy individuals and 175 sera from Chagas”™ patients (70 by xenodiagnosis). Cross-reactivity was tested using 289 sera from patients who had a parasitological diagnosis of a disease known to induce antigenic responses towards T. cruzi. All of these sera were tested with our AgA-ELISA and with 3 commercial diagnosis kits. To evaluate the agreement of results between our AgA-ELISA and a “gold standard” test for Chagas, we tested 566 sera from an endemic area. Results: sensitivity and specificity were 100%; cross-reactivity was the lowest compared with commercial kits. Overall agreement with the gold standard test was excellent (kappa=0.92). AgA-ELISA exhibits levels of sensitivity, specificity and cross-reactivity comparable or superior to those shown, obtained with the commercial kits used in our country, while being at least 10 times less expensive. This balance between diagnostic accuracy and cost makes AgA-ELISA useful for blood bank screening in poor regions of the world suffering from Chagas”™ disease. Further validations of this antigenic formulation in other countries are necessary.